Applicators and methods to achieve precise spatial control of the treatment zone during microwave ablation - Pfannenstiel, Austin (Kansas State University, 2020)
Cancer is a large and growing societal concern. According to the World Health Organization, one in five men and one in six women worldwide will develop cancer during their lifetime. However, some patients cannot be treated with established therapeutic modalities such as surgery, radiation, or chemotherapy because of challenges with performing these complex procedures for some tumors, the potential for complication due to other medical conditions, and/or dose limiting toxicities. Thermal ablation offers a low-cost, minimally invasive therapy that can be used to treat tumors, usually as an outpatient procedure. Of the possible thermal ablation energy modalities, microwave ablation (MWA) is gaining increasing clinical adoption due to its ability to rapidly heat large volumes of tissue, radiate through charred or other high impedance tissues, and avoid expensive and cumbersome ancillary equipment. However, a significant problem limiting MWA technologies is that the growth of the thermal treatment zone cannot be precisely targeted or visualized in real time and it is therefore extremely difficult to reliably ensure the entire tumor is fully treated without also causing unintended thermal injury to adjacent critical anatomy. This limitation leaves doctors with a difficult choice of risking undertreatment and disease recurrence or risking overtreatment and damage to critical healthy anatomy that may cause pain or life-threatening complications. The fundamental technical barrier to precise targeting, and therefore to broader MWA clinical acceptance is that all currently available MWA systems can only produce a roughly spherical, ellipsoidal, or teardrop-shaped treatment zone centered on the axis near the tip of the applicator, which is not suitable for treating tumors with irregular shapes or those located near critical anatomy. This dissertation focuses on the development of a MWA applicator and methods to achieve precise spatial control of the treatment zone during microwave ablation in diverse tissue targets. A 14-gauge directional MWA (DMWA) applicator design is presented which would allow the physician to instead place the applicator alongside the tumor and direct heat towards the target and away from nearby sensitive tissues. DMWA may also be used with multiple applicators to “bracket” the tumor and clinical margin to enable a procedure with less chance of complications and disease recurrence, or applied on the surface of a target aiming inward in an even less-invasive non-penetrating approach. Coupled electromagnetic-bioheat transfer computational models were used for design and simulation of this DMWA applicator. Proof-of-concept applicators were evaluated in ex vivo liver at 60, 80, and 100 W generator settings for 3, 5 and 10 minutes (n=4 per combination) and in vivo tissue at 80 and 100 W generator settings for 5 or 10 minutes (n=2 or 3 per combination). Mean ex vivo ablation forward depth was 8–15.5 mm. No backward heating was observed at 60 W, 3–5 minutes; directivity (the ratio of forward ablation depth to backward ablation depth) was 4.7–11.0 for the other power and time combinations. In vivo ablation forward depth was 10.3–11.5 mm and directivity was 11.5-16.1. No visible or microscopic thermal damage to non-target tissues in direct contact with the back side of the applicator was observed. As the resulting thermal treatment zone from MWA is comprised of regions exposed to direct electromagnetic heating as well as regions indirectly heated by thermal conduction from the temperature gradients created during thermal ablation, using excessive treatment power or duration during a DMWA procedure may still result in undesired heating of non-target sectors through the thermally conductive surrounding tissues. A method is presented to cycle microwave power on and off to allow blood perfusion in the surrounding tissue to cool the margins of the treatment zone and improve the directivity of the DMWA procedure. Coupled electromagnetic-bioheat transfer computational models were used to evaluate equivalent energy delivery power pulsing protocols with periods of 5, 10, or 20 seconds, duty cycles of 50, 75, or 100%, and a 100 W generator power setting. A 10 second period, 70% duty cycle, 80 W generator setting power pulsing protocol in ex vivo liver showed a 51.7% reduction in the backward ablation depth, a 2.3% increase in the forward ablation depth, and a 115.2% increase in the directivity ratio. A 10 second period, 70% duty cycle, 100 W generator setting power pulsing protocol in in vivo liver showed a 40.1% reduction in the backward ablation depth, a 1.0% reduction in the forward ablation depth, and a 59.6% increase in the directivity ratio. Once many common types of cancer metastasize, a common site to which they spread is bone. Should cancer form in the vertebral bodies, the resulting tumor growth can cause significant pain and neurological problems including paralysis. Due to the proximity of a significant amount of critical anatomy, including the spinal cord and other nerves, treating these tumors can be exceedingly challenging. DMWA may offer the ability to provide enough spatial control of the ablation zone to attempt more palliative treatments of vertebral tumors in proximity to critical nerves and the spinal cord. However, there is limited published literature describing the interactions of microwave energy in bone tissues in detail; of specific importance is the degree of microwave absorption/transmission in bone tissue relative to tissues types that would comprise metastatic disease and how that may affect the resultant size and shape of the resultant treatment zone. Presented are three-dimensional simulations of spinal DMWA treatment zones based on coupled electromagnetic-bioheat transfer computational models with tissue domains that mimic the anatomical dimensions and the biophysical properties of each different type of tissue, including cortical bone, cancellous bone, spinal cord, cartilage, and metastatic and primary tumor. DMWA experimental ablations at 80 or 120 W generator settings for 3.5 or 5 minutes with two fiber optic temperature sensors in ex vivo vertebrae showed a temperature rise of 33.5 – 63.2 °C in the vertebral body 9.5 mm from the DMWA applicator (T1) and a temperature rise of 10.8 – 32.3 °C in the spinal canal 2.5 mm from the backside of the applicator (T2). A computational model with static bone tissue biophysical properties was able to predict the temperature change in the forward direction within 3 – 7% and in the backward direction within 11 – 37% of the experimental observation. This computational model was further modified to include tissue-specific perfusion values and demonstrated two DMWA applicators operated at 80 W generator setting for 5 minutes could heat the entirety of a 2 cm metastatic tumor in the vertebral body to ablative temperature (55 °C) without exceeding 45 °C in the spinal canal.
Keywords: thermal ablation; microwave antenna; directional antenna; medical deviceMicrowave ablation